IDENTIFIKASI FAKTOR-FAKTOR PEMICU KEKERASAN DALAM RUMAH TANGGA DI KOTA DENPASAR - ARIFIANTI, LAILY A.A.; JAYANEGARA, KETUT; GANDHIADI, G.K.; KENCANA, EKA N. (E-Jurnal Matematika; Vol 6 No 1 (2017), 2017)
Family or domestic violence is meant as a pattern of someone behavior that abuse his/or her power against another member(s) in a family or domestic setting. Knowing the underlying factors that trigger family violence are important to keep family members form a harmonious relationship. This work is aimed to elaborate those factors. By analyzing primary data from 120 respondents whom witness and well informed about family violence in their neighborhoods, factor analyzes is applied. Data are collected by using tested questionnaires. The results showed they were six underlying factors for family violence with total accounted for all factors were 65.19 percent.  Those factors are (a) social relationship, (b) job description, (c) past experience, (d) supporting factor, (e) economics’ status, and (f) harmonious relationship level. From these factors, social relationship dominates the others with variance explained for family violence as much as 21.39 percent.
Keywords: family violence; factor analysis; social relationship